2016
DOI: 10.1007/s10014-016-0264-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological differences between variants of the NAB2–STAT6 fusion gene in solitary fibrous tumors of the meninges and extra-central nervous system

Abstract: Investigations on the NAB2-STAT6 fusion gene in solitary fibrous tumors (SFTs) and hemangiopericytomas (HPCs) have increased since its discovery in 2013. Although several SFTs reported without NAB2-STAT6 fusion gene analysis, we reviewed 546 SFTs/HPCs with NAB2-STAT6 fusion gene analysis in this study and investigated differences between the gene variants. In total, 452 cases tested positive for the NAB2-STAT6 fusion gene, with more than 40 variants being detected. The most frequent of these were NAB2 exon 6-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 33 publications
1
25
0
1
Order By: Relevance
“…Further advances in grading SFT/HPC might be possible by integrating molecular information into specific grading subgroups. For example, different NAB2‐STAT6 gene fusion variants in soft tissue SFTs are reportedly correlated to different clinical outcomes, and TERT promoter mutations have also been associated with adverse prognosis . The prognostic relevance of these molecular aberrations in CNS SFTs/HPCs needs to be further investigated in a larger number of tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Further advances in grading SFT/HPC might be possible by integrating molecular information into specific grading subgroups. For example, different NAB2‐STAT6 gene fusion variants in soft tissue SFTs are reportedly correlated to different clinical outcomes, and TERT promoter mutations have also been associated with adverse prognosis . The prognostic relevance of these molecular aberrations in CNS SFTs/HPCs needs to be further investigated in a larger number of tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that sarcoma patients whose tumours were interrogated by NGS as part of their clinical management received the option of access to targeted agents in their treatment [31]. This is because a difference in clinical outcome may be predicted by one or more of the following: firstly, incidence of a specific fusion; next, the presence of one or more variants of a fusion; or finally, the presence of one of a heterogeneous group of unrelated fusions [32, 33]. More significantly, as the cases in discussion are rare paediatric tumours, an isolated fusion found in a single patient can be important, especially for future therapeutic targeting [3].…”
Section: Discussionmentioning
confidence: 99%
“…20 Even if they are associated with grading, the types of fusion variants are not associated with prognosis, recurrence-free survival, or overall survival. 2,12,20 Malignant progression may be just one of several mechanisms provoking recurrence and metastasis. There is a strong tendency for Grade III tumors to produce more metastases and a shorter overall survival and recurrencefree interval in some studies (for example, overall survival of 256 months vs 114 months and recurrence-free interval of 95 months vs 59 months for Grade III vs lower-grade tumors, respectively 10 ).…”
Section: Discussionmentioning
confidence: 99%